Tissue reaction against implantation of nanocomposite and giomers - Vilvarajah, Anusha S; Djustiana, Nina; Widyaputra, S. Sunardhi (Padjadjaran Journal of Dentistry, 2011)
Dentistry today has inherited technological advancement from other Dental Material sciences, examples are Nanocomposite and Giomers. Nanocomposites and Giomers are common materials used in Dentistry. But what are the implications when these materials are used in practice? The aim for this the study shows the analysis of tissue reaction due to implantation of Nanocomposite and Giomers. The subcutaneous tissue of a mouse is substituted with the human gum tissues. In the experimental group, Nanocomposite and Giomers were implanted in the subcutaneous tissue abdomen region in mice. The slides were made from the surrounding of implantation for both experimental and control groups. The evaluation of the effects of the implant is done in a time interval. Evaluated time intervals are 24 hours, 7" day, 14th day, 21st day and 28th day respectively. The amounts of inflammatory cells formation in both groups were compared.Once the results of the inflammatory cells are evaluated in the given time interval for Nanocomposite, Giomer, and control group then they are statistically analyzed. The statistics used in the experiments is Mann-Whitney and Wilcoxon. The conclusion of this research showed that statistically significant differences on lymphocytes value between treatment and control group.